Pengaruh Laju Alir Terhadap Penyerapan Ion Logam Cd2+ Menggunakan Biomassa Kulit Langsat (Lansium domesticum) dengan Metode Kolom - Ideal, Flami Luthfianisa; Kurniawati, Desy; Mawardi, Mawardi; Hardeli, Hardeli (Periodic, 2024)
Increasing industrial activities have a negative impact on the ecosystem. One of them is environmental pollution. Heavy metals can be found in industrial waste whose presence can endanger living things around the industrial environment. Overcoming the presence of heavy metal ions in industrial waste can be done by biosorption methods. Biosorption is one of the strategies that can be utilized to adsorb heavy metal levels contained in wastewater. Langsat shell was used as biomass to adsorb Cd2+ metal ions using column method.  This study was conducted to determine the effect of flow rate on the absorption of Cd2+ metal ions. The results showed that the optimal absorption of Cd2+ metal ions by langsat shell occurred at a flow rate of 1 mL /  min with an absorption capacity of 16.5425 mg/gram.